Characterizing diamond detectors for various dose and dose rate measurements in scanned carbon and oxygen beams - Karle, Celine; Verona-Rinati, Gianluca; Brons, Stephan; Cee, Rainer; Scheloske, Stefan; Schömers, Christian; Kranzer, Rafael; Haberer, Thomas; Marinelli, Marco; Mairani, Andrea; Tessonnier, Thomas (Medical physics, 2025)
Background: The emerging FLASH radiotherapy technique employs “Ultra-High Dose Rate” (UHDR) irradiations and offers the potential to spare normal tissue while maintaining iso-effective tumor treatment. Given the physical and biological advantages inherent to high “Linear Energy Transfer” (LET) particles, the combination of UHDR and high LET has the capability to enhance the normal tissues sparing, as indicated by initial in vivo trials. However, to ensure a safe implementation of this combined modality, it is essential to establish robust dosimetric protocols utilizing dose-, dose rate-, and LET-independent detectors. Purpose The objective of this study is to characterize the dose, dose rate, and LET dependency of two diamond detectors with high LET carbon and oxygen ion irradiation under “Standard Dose Rate” (SDR) and UHDR conditions. Methods: The “microDiamond” (mD) and a “flashDiamond” (fD) prototype were benchmarked against measurements with a monitoring ionization chamber, Advanced Markus chamber (AMC), and simulations for carbon and oxygen irradiation, with energies of 274.98 MeV/u and 325.98 MeV/u under SDR and UHDR conditions. First, the entire depth-dose profiles obtained during SDR irradiations and the partial in-depth profiles of the Bragg peak region in UHDR were compared to the corresponding simulation values. Secondly, the linearity of the diamond detector response during dose escalation measurements was investigated for both dose rates. Results: The two detectors exhibited alignment with the simulated depth-dose distributions for oxygen and carbon irradiations across both dose rate conditions. The mD overestimated the dose values for carbon and oxygen measurements. This overestimation increased with “dose-averaged LET” (LETd) during SDR irradiation and maintained a stable value of 5% for UHDR. Meanwhile, the fD demonstrated a high degree of agreement with the simulation, with a maximum discrepancy of 5% across all irradiation modalities in the plateau and “Bragg Peak” (BP). Deviations were observed in the BP fall-off region, while both diamond detectors exhibited a strong alignment with the AMC measurements. Furthermore, both detectors exhibited dose linearity under SDR and UHDR irradiation for both carbon and oxygen irradiation, with a coefficient of determination (R2) above 0.99. Conclusion: In the context of heavy ion carbon and oxygen irradiation in UHDR and SDR, the two diamond detectors demonstrated dose-rate independence. While the mD exhibited a tendency to overestimate dose values with increasing LETd, the fD was found to be LET-independent. The fD appears to offer accurate and reliable dose assessments for UHDR heavy ion experiments.
Gesehen am 17.09.2025